Graphene copper composite material and preparation method and application thereof

By in situ carbonization on the surface of high-purity copper powder, and optimizing the structure through the hot press sintering process, the problems of poor conductivity and low strength of graphene silver materials in the prior art are solved, and graphene copper composite materials with high conductivity and high tensile strength are realized, which are suitable for high-performance electronic products and transmission equipment.

CN119634724APending Publication Date: 2025-03-18CHINA ELECTRIC POWER RESEARCH INSTITUTE CO LTD +2
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411661376.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-20
Publication Date
2025-03-18

AI Technical Summary

Technical Problem

The graphene copper materials prepared by in-situ growth method in the prior art have problems of poor conductivity and low strength, and cannot meet the application requirements.

Method used

High-purity copper powder is used as the base material to carbonize in situ under a carbon source and protective atmosphere to form graphene, and the material structure is optimized through the hot pressing sintering process to form graphene copper composite material with high conductivity and tensile strength.

Benefits of technology

It significantly improves the conductivity and tensile strength of graphene copper composite materials, and the performance indicators meet the conductivity ≥102% IACS and the tensile strength ≥180MPa. It is suitable for electronic products and transmission equipment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119634724A_ABST
    Figure CN119634724A_ABST
Patent Text Reader

Abstract

The invention discloses a graphene copper composite material and a preparation method and application thereof.The preparation method of the graphene copper composite material comprises the following steps that copper powder is subjected to in-situ carbonization under a carbon source and a protective atmosphere so that graphene can be formed on the surface of the copper powder, graphene copper powder is obtained, and the purity of the copper powder is larger than or equal to 99.9%; and the copper powder and the graphene copper powder are mixed for hot pressed sintering, and the graphene copper composite material is obtained. Wherein the graphene copper composite material comprises the following components in percentage by mass: 0.5-25wt% of graphene copper powder and the balance of copper powder; the content of carbon in the graphene copper powder is 0.05 to 0.5 weight percent. According to the graphene copper composite material and the preparation method and application thereof, the conductivity and tensile strength of the composite material can be remarkably improved, and the performance indexes meet the requirements that the conductivity is larger than or equal to 102% IACS, and the tensile strength is larger than or equal to 180 MPa.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of composite materials, and in particular to a graphene copper composite material and a preparation method and application thereof. Background Art

[0002] With the rapid development of science and technology, electronic products are gradually developing towards miniaturization and high performance. This trend has brought new challenges to materials science, especially in the field of conductive composite materials. Traditional copper materials are widely used in various electronic devices and power transmission systems due to their good electrical conductivity and mechanical properties. However, with the continuous improvement of equipment performance requirements, relying solely on copper materials can no longer meet the needs of future high-performance electronic products. Therefore, research and development of new room temperature high-conductivity composite materials has become a hot topic in the field of scientific research.

[0003] In recent years, graphene, as a new type of two-dimensional nanomaterial, has attracted widespread attention for its unique electronic, thermal and mechanical properties. Graphene not only has ultra-high electrical and thermal conductivity, but also has excellent mechanical properties. It is considered to be an ideal choice for improving the electrical conductivity and mechanical properties of traditional copper materials. Graphene is combined with copper materials to prepare high-conductivity graphene-copper composite materials. By introducing graphene and optimizing its interface interaction with the copper matrix, the electrical conductivity and mechanical properties of the composite material can be improved.

[0004] At present, the methods for preparing graphene copper composite materials include mechanical mixing method, molecular mixing method, in-situ growth method, etc. Among them, the in-situ growth method is easy to operate and can effectively reduce the agglomeration problem caused by the addition of carbon sources such as graphene. However, the graphene obtained by the existing in-situ growth method still has a large number of defects or the high cost of high-quality graphene, resulting in the electrical conductivity and strength of the composite material failing to meet the application requirements. Therefore, it is urgent to develop an economically feasible room temperature high-conductivity graphene copper composite material. Summary of the invention

[0005] The purpose of the present invention is to solve the technical problem that the graphene copper material prepared by the in-situ growth method in the prior art has poor conductivity and low strength and cannot meet the application requirements.

[0006] The purpose of the present invention is to adopt the following technical solutions to achieve:

[0007] The present invention provides a method for preparing a graphene copper composite material, comprising the following steps:

[0008] In-situ carbonization of copper powder is performed under a carbon source and a protective atmosphere to form graphene on the surface of the copper powder to obtain graphene copper powder, wherein the purity of the copper powder is ≥99.9%;

[0009] The copper powder and the graphene copper powder are mixed and hot-pressed to obtain the graphene copper composite material;

[0010] The graphene copper composite material comprises, by weight percentage, 0.5-25wt% of graphene copper powder and the remainder of copper powder; the carbon content in the graphene copper powder is 0.05-0.5wt%.

[0011] Preferably, the graphene copper composite material comprises, in terms of mass percentage, 5-25wt% of graphene copper powder and the remainder of copper powder; the carbon content in the graphene copper powder is 0.12-0.5wt%.

[0012] Preferably, in terms of mass percentage, the graphene copper composite material comprises: 5wt% of graphene copper powder and the remainder of copper powder; the carbon content in the graphene copper powder is 0.12wt%.

[0013] Preferably, the copper powder is a micron-sized powder with a particle diameter of 1 to 50 μm, preferably a particle diameter of 3 to 8 μm.

[0014] Preferably, the in-situ carbonization temperature is 700-1000° C., and the carbonization time is 20-60 min.

[0015] Preferably, the hot pressing sintering temperature is 700-1000° C., the hot pressing pressure is 30-100 MPa, and the sintering time is 10-30 min.

[0016] Preferably, before the step of in-situ carbonizing the copper powder under a carbon source and a protective atmosphere to form graphene on the surface of the copper powder, the method further comprises:

[0017] The copper powder is subjected to reduction treatment in a reducing atmosphere so that the purity of the copper powder is maintained at not less than 99.9%.

[0018] Preferably, the reduction treatment temperature is 150-300° C., and the treatment time is 30-60 min.

[0019] Preferably, before the step of in-situ carbonizing the copper powder under a carbon source and a protective atmosphere to form graphene on the surface of the copper powder, the method further comprises:

[0020] The carbon source and the copper powder are mixed and dissolved in a solvent, and ultrasonic dispersion treatment is performed to obtain a uniform mixture. The mixture is dried and crushed to obtain copper powder coated with the carbon source.

[0021] Preferably, the solvent is a mixed solution of water and ethanol in a volume ratio of 1:1 to 4.

[0022] Preferably, in the drying process, the drying temperature is 100-150° C. and the drying time is 1-2 hours.

[0023] Preferably, the carbon source is one or more of sucrose, fructose, glucose and maltose.

[0024] Preferably, the protective atmosphere is an inert gas, and the reducing atmosphere is a mixed gas consisting of an inert gas and hydrogen.

[0025] Preferably, the inert gas flow rate is 0.7 to 1 L / min, and the hydrogen flow rate is 0.3 to 1 L / min.

[0026] Based on the same inventive concept, the present invention also provides a graphene copper composite material prepared by the above preparation method.

[0027] Based on the same inventive concept, the present invention also provides an application of a graphene copper composite material in electronic products and / or power transmission equipment.

[0028] Compared with the prior art, the present invention has the following beneficial effects:

[0029] The preparation method of the graphene copper composite material provided by the present invention adopts high-purity copper powder (purity of the copper powder is ≥99.9%) as a base material, forms graphene on the surface of the copper powder by in-situ carbonization of a carbon source to obtain graphene copper powder for coating, and sintering and densifying the graphene copper powder and the copper powder by a sintering process to obtain the graphene copper composite material. The preparation method of the invention utilizes the high catalytic property of the surface of high-purity copper to fully decompose and carbonize the carbon source to form a high-quality graphene carbon layer coated on the surface of the copper particles, so that the graphene copper composite material has high electrical conductivity. At the same time, the carbon content in the graphene copper powder and the ratio of the copper powder to the graphene copper powder are optimized, and the microstructure and interface structure are adjusted through an in-situ growth process and a sintering process, so that the surface of the copper powder forms a graphene carbon layer with obvious wrinkle characteristics, and on the basis of maintaining the high carrier concentration of copper, the high electrical conductivity and dislocation strengthening mechanism of graphene are utilized to significantly improve the electrical conductivity and tensile strength of the composite material. The performance indicators of the graphene copper composite material obtained by the preparation method of the invention meet the requirements of electrical conductivity ≥102%IACS and tensile strength ≥180MPa. The preparation method of the invention has a simple process, is easy to control, is easy to realize industrial production and application, and is suitable for electronic products and power transmission equipment. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 The present invention is a flow chart of a method for preparing a graphene copper composite material;

[0031] Figure 2 This is an electron microscope (SEM) scanning image of the graphene copper composite material of the present invention;

[0032] Figure 3 This is a Raman spectrum analysis spectrum of the graphene copper composite material of the present invention. DETAILED DESCRIPTION

[0033] Below in conjunction with the drawings and Examples, the specific embodiments of the present invention are described in further detail. The following examples are used to illustrate the present invention, but are not used to limit the scope of the present invention. Any product identical or similar to the present invention obtained by combining the features of the present invention and other prior arts under the enlightenment of the present invention, all falls within the protection scope of the present invention. The specific experimental steps or conditions not indicated in the embodiments can be carried out according to the operation or conditions of the conventional experimental steps described in the documents in this area. The reagents used or the instruments not indicated by the manufacturer are all conventional reagent products that can be obtained by commercial purchase.

[0034] Example 1

[0035] The embodiment of the present invention provides a graphene copper composite material, which comprises, by weight percentage, 0.5wt% graphene copper powder and the remainder copper powder; the carbon content in the graphene copper powder is 0.12wt%, and the purity of the copper powder is ≥99.9%.

[0036] The preparation method of the graphene copper composite material of the embodiment of the present invention is as follows: Figure 1 As shown, the following steps are included:

[0037] S101: performing reduction treatment on the copper powder in a reducing atmosphere so that the purity of the copper powder is maintained at not less than 99.9%;

[0038] S102: mixing and dissolving the carbon source and the copper powder in a solvent, performing ultrasonic dispersion treatment to obtain a uniform mixture, and drying and pulverizing the mixture to obtain copper powder coated with the carbon source;

[0039] S103: in-situ carbonizing the copper powder under a carbon source and a protective atmosphere to form graphene on the surface of the copper powder to obtain graphene copper powder;

[0040] S104: mixing the copper powder and the graphene copper powder and performing hot pressing and sintering to obtain the graphene copper composite material.

[0041] In the above S101, this embodiment uses high-purity copper with a purity of ≥99.9% as the matrix material, and utilizes the high reducibility and high carrier concentration of copper to make the prepared graphene copper composite material have high conductivity. Since high-purity copper is easily oxidized in an air environment, before in-situ carbonization, the copper powder needs to be reduced in a reducing atmosphere to keep the purity of the copper powder not less than 99.9%.

[0042] Micron-sized copper powder is selected, and the particle diameter is in the range of 1 to 50 μm, preferably 3 to 8 μm. The present embodiment finally prepares a graphene copper composite material. Combining graphene with high electron mobility with copper particles with high carrier concentration makes the composite material have more excellent mechanical properties and high conductivity, and can be widely used in electronic equipment and power transmission systems to meet the high performance requirements of electronic products and power transmission lines.

[0043] The specific process of reduction treatment is as follows: copper powder is loaded into a crucible, placed in a tube furnace, and heated to 200°C and maintained for 60 minutes in a mixed gas consisting of argon with a flow rate of 0.7 to 1 L / min and hydrogen with a flow rate of 0.3 to 1 L / min to reduce the copper powder; after the reduction is completed, in order to prevent the copper powder from being re-oxidized, the tube furnace is cooled to room temperature under the same protective atmosphere; then the reduced copper powder is taken out of the tube furnace, mechanically ground and crushed, and screened through sieves of different mesh sizes to obtain uniform powder.

[0044] In the above S102, this embodiment uses sucrose as a carbon source, and by reasonably formulating the mass of sucrose and the copper powder after reduction treatment, the carbon content in the graphene copper obtained after in-situ carbonization is maintained at 0.12wt%.

[0045] The solvent is a mixed solution composed of water and ethanol, and the particle dispersion effect is better than that of a solvent using only water; the carbon source and copper powder are mixed and dissolved in the solvent, and ultrasonic dispersion treatment is performed, the purpose of which is to allow the carbon source to be evenly dispersed and coated on the surface of the copper powder, so as to facilitate subsequent in-situ carbonization to obtain a graphene layer with uniform thickness, so that the performance of the prepared graphene copper can reach a better and more stable state.

[0046] The specific process of dissolution, ultrasonic dispersion, drying and pulverization in this embodiment is as follows: the carbon source is dissolved in a mixed solution of water and ethanol with a volume ratio of 1:2, and the mixed solution is ultrasonically dispersed using an ultrasonic probe for 5 minutes. The mixed solution after ultrasonic treatment is then placed in a tube furnace, heated to 120°C in a protective atmosphere of argon (with an inlet flow rate of 1 L / min), kept warm for 1.5 hours, and dried to remove the solvent and moisture. After drying, the powder is cooled to room temperature, taken out of the tube furnace and transferred to an alumina crucible for mechanical grinding and pulverization, and then screened through sieves of different mesh sizes to obtain a uniform copper powder coated with the carbon source.

[0047] In the above S103, the copper powder coated with the carbon source obtained above is in-situ carbonized, that is, the surface of the copper powder is in-situ carbonized under a carbon source and a reducing atmosphere, and graphene is in-situ grown on the surface of the copper powder to obtain graphene copper powder. The specific process is: the copper powder coated with the carbon source is placed in a tube furnace, and graphitized at a temperature of 800°C for 40 minutes in a protective atmosphere of argon (1L / min). After cooling to room temperature, the powder is taken out of the tube furnace, mechanically ground and crushed, and then screened through sieves of different mesh sizes to obtain uniform graphene copper powder.

[0048] In the above S104, the copper powder after the reduction treatment and the prepared graphene copper powder are mixed and hot pressed and sintered to prepare the graphene copper composite material. The hot pressing and sintering process can optimize the material density, reduce the interface distance between copper and graphene, and thus improve the conductivity.

[0049] The specific process of the hot pressing sintering process is as follows: the copper powder and graphene copper powder are mechanically stirred, mixed evenly, and then placed in a graphite mold for hot pressing sintering. The sintering temperature is 800°C, the hot pressing pressure is 100MPa, and the sintering time is 20min. The sample obtained by hot pressing sintering is surface cleaned with silicon carbide paper to remove any surface unevenness or residual debris, and finally a graphene copper composite material is obtained.

[0050] Example 2

[0051] The embodiment of the present invention provides a graphene copper composite material, which comprises, by weight percentage, 2.5wt% graphene copper powder and the remainder copper powder; the carbon content in the graphene copper powder is 0.12wt%, and the purity of the copper powder is ≥99.9%. The preparation method of the graphene copper composite material of the embodiment of the present invention is the same as that of embodiment 1.

[0052] Example 3

[0053] The embodiment of the present invention provides a graphene copper composite material, which comprises, by weight percentage, 5wt% graphene copper powder and the remainder copper powder; the carbon content in the graphene copper powder is 0.12wt%, and the purity of the copper powder is ≥99.9%. The preparation method of the graphene copper composite material of the embodiment of the present invention is the same as that of embodiment 1.

[0054] Example 4

[0055] The embodiment of the present invention provides a graphene copper composite material, which includes, by weight percentage, 25wt% graphene copper powder and the remainder copper powder; the carbon content in the graphene copper powder is 0.12wt%, and the purity of the copper powder is ≥99.9%. The preparation method of the graphene copper composite material of the embodiment of the present invention is the same as that of embodiment 1, except that maltose is used as a carbon source in this embodiment.

[0056] Example 5

[0057] The embodiment of the present invention provides a graphene copper composite material, which comprises, by weight percentage, 5wt% graphene copper powder and the remainder copper powder; the carbon content in the graphene copper powder is 0.05wt%, and the purity of the copper powder is ≥99.9%. The preparation method of the graphene copper composite material of the embodiment of the present invention is the same as that of embodiment 1.

[0058] Example 6

[0059] The embodiment of the present invention provides a graphene copper composite material, which includes, by weight percentage, 5wt% graphene copper powder and the remainder copper powder; the carbon content in the graphene copper powder is 0.5wt%, and the purity of the copper powder is ≥99.9%. The preparation method of the graphene copper composite material of the embodiment of the present invention is the same as that of embodiment 1, except that maltose is used as a carbon source in this embodiment.

[0060] Example 7

[0061] The embodiment of the present invention provides a graphene copper composite material, which includes, by weight percentage, 5wt% graphene copper powder and the remainder copper powder; the carbon content in the graphene copper powder is 0.12wt%, and the purity of the copper powder is ≥99.9%. The preparation method of the graphene copper composite material of the embodiment of the present invention is the same as that of embodiment 1, except that maltose is used as a carbon source in this embodiment.

[0062] Example 8

[0063] The embodiment of the present invention provides a graphene copper composite material, which includes, by weight percentage, 5wt% graphene copper powder and the remainder copper powder; the carbon content in the graphene copper powder is 0.12wt%, and the purity of the copper powder is ≥99.9%. The preparation method of the graphene copper composite material of the embodiment of the present invention is the same as that of embodiment 1, except that glucose is used as a carbon source in this embodiment.

[0064] Example 9

[0065] The embodiment of the present invention provides a graphene copper composite material, which includes, by weight percentage, 5wt% graphene copper powder and the remainder copper powder; the carbon content in the graphene copper powder is 0.12wt%, and the purity of the copper powder is ≥99.9%. The preparation method of the graphene copper composite material of the embodiment of the present invention is the same as that of embodiment 1, except that fructose is used as a carbon source in this embodiment.

[0066] Example 10

[0067] The components, proportions and preparation method of a graphene copper composite material provided in an embodiment of the present invention are the same as those in Example 3, except that: in S101, the reduction treatment temperature of the copper powder is 150°C.

[0068] Embodiment 11

[0069] The components, proportions and preparation method of a graphene copper composite material provided in an embodiment of the present invention are the same as those in Example 3, except that: in S101, the reduction treatment temperature of the copper powder is 300°C.

[0070] Example 12

[0071] The components, proportions and preparation method of a graphene copper composite material provided in an embodiment of the present invention are the same as those in Example 3, except that: in S101, the reduction treatment time of the copper powder is 30 minutes.

[0072] Example 13

[0073] The components, proportions and preparation method of a graphene copper composite material provided in an embodiment of the present invention are the same as those in Example 3, except that: in S101, the reduction treatment time of the copper powder is 45 minutes.

[0074] Embodiment 14

[0075] The components, proportions and preparation method of a graphene copper composite material provided in an embodiment of the present invention are the same as those in Example 3, except that: in S102, the drying temperature is 100°C.

[0076] Embodiment 15

[0077] The components, proportions and preparation method of a graphene copper composite material provided in an embodiment of the present invention are the same as those in Example 3, except that: in S102, the drying temperature is 150°C.

[0078] Example 16

[0079] The components, proportions and preparation method of a graphene copper composite material provided in an embodiment of the present invention are the same as those in Example 3, except that: in S102, the drying time is 1 hour.

[0080] Embodiment 17

[0081] The components, proportions and preparation method of a graphene copper composite material provided in an embodiment of the present invention are the same as those in Example 3, except that: in S102, the drying time is 2 hours.

[0082] Embodiment 18

[0083] The components, proportions and preparation method of a graphene copper composite material provided in an embodiment of the present invention are the same as those in Example 3, except that: in S103, the in-situ carbonization temperature is 700°C.

[0084] Embodiment 19

[0085] The components, proportions and preparation method of a graphene copper composite material provided in an embodiment of the present invention are the same as those in Example 3, except that: in S103, the in-situ carbonization temperature is 1000°C.

[0086] Embodiment 20

[0087] The components, proportions and preparation method of a graphene copper composite material provided in an embodiment of the present invention are the same as those in Example 3, except that: in S103, the in-situ carbonization time is 20 minutes.

[0088] Embodiment 21

[0089] The components, proportions and preparation method of a graphene copper composite material provided in an embodiment of the present invention are the same as those in Example 3, except that: in S103, the in-situ carbonization time is 60 minutes.

[0090] Embodiment 22

[0091] The components, proportions and preparation method of a graphene copper composite material provided in an embodiment of the present invention are the same as those in Example 3, except that: in S104, the sintering temperature is 700°C.

[0092] Embodiment 23

[0093] The components, proportions and preparation method of a graphene copper composite material provided in an embodiment of the present invention are the same as those in Example 3, except that: in S104, the sintering temperature is 1000°C.

[0094] Embodiment 24

[0095] The components, proportions and preparation method of a graphene copper composite material provided in an embodiment of the present invention are the same as those in Example 3, except that: in S104, the hot pressing pressure is 30 MPa.

[0096] Embodiment 25

[0097] The components, proportions and preparation method of a graphene copper composite material provided in an embodiment of the present invention are the same as those in Example 3, except that: in S104, the hot pressing pressure is 60 MPa.

[0098] Embodiment 26

[0099] The components, proportions and preparation method of a graphene copper composite material provided in an embodiment of the present invention are the same as those in Example 3, except that: in S104, the sintering time is 10 minutes.

[0100] Embodiment 27

[0101] The components, proportions and preparation method of a graphene copper composite material provided in an embodiment of the present invention are the same as those in Example 3, except that: in S104, the sintering time is 30 minutes.

[0102] Embodiment 28

[0103] The components, proportions and preparation method of a graphene copper composite material provided in an embodiment of the present invention are the same as those in Example 3, except that: in S102, the volume ratio of ethanol to water is 1:1.

[0104] Embodiment 29

[0105] The components, proportions and preparation method of a graphene copper composite material provided in an embodiment of the present invention are the same as those in Example 3, except that: in S102, the volume ratio of ethanol to water is 4:1.

[0106] Comparative Example 1

[0107] High-purity copper (purity ≥ 99.9%) was used as a comparative example.

[0108] The present invention is further explained below by testing the graphene copper composite material of the above embodiment and the high purity copper of the comparative example.

[0109] 1. Scanning electron microscope detection

[0110] The graphene copper composite material obtained in Example 3 was scanned by a scanning electron microscope (SEM) to obtain an electron microscope scanning image as shown in FIG. Figure 2 As shown, Figure 2 Figure b is a partial enlarged view of Figure a, and the arrows point to "Carbon sheets" which represent graphene carbon layers. Figure 2 It can be seen that the surface of the copper powder is coated with a graphene carbon layer, indicating that the carbon source can be effectively carbonized to form graphene, and the graphene has a lamellar structure with obvious wrinkle characteristics, indicating that it has a good coating effect. The formed graphene structure is enhanced and has high mechanical strength and toughness. The wrinkles will increase the surface area of ​​​​graphene, enhance the interaction with other substances, and have good adsorption properties.

[0111] 2. Raman spectroscopy analysis and detection

[0112] The graphene copper composite material obtained in Example 3 was subjected to Raman spectroscopy analysis by a Raman spectrometer to obtain an analysis spectrum as shown in FIG. Figure 3 As shown, the horizontal axis "Raman shift" represents the Raman shift. Figure 3 It can be seen that the Raman spectrum shows two common peaks of graphene: at 1376cm -1 The D peak is located at 1600cm -1The intensity ratio of the two peaks is D / I G The calculated value is 0.77, indicating that the graphene is less disordered and the generated graphene has fewer structural defects.

[0113] 3. Material performance testing

[0114] The room temperature conductivity and tensile strength tests were performed on the graphene copper composite materials obtained in Examples 1 to 9 and the high purity copper in Comparative Example 1, respectively. The room temperature conductivity test was performed using GB-T 3930-2008 (DC bridge for measuring resistance), and %IACS is the international standard conductivity of annealed copper; the tensile strength test was performed using GB / T228-2002 standard. The test results are shown in Table 1 (Examples 1 to 9), Table 2 (Examples 10 to 19), and Table 3 (Examples 20 to 29).

[0115] Table 1: Effects of different group ratios on material properties

[0116]

[0117] Table 2: Effects of different process conditions on material properties

[0118]

[0119]

[0120] Table 3: Effects of different process conditions on material properties

[0121]

[0122] From the above Tables 1 to 3, we can see that:

[0123] 1. The tensile strength and electrical conductivity of the graphene copper composite material of the embodiment of the present invention are significantly better than those of pure copper. The performance indicators of the graphene copper composite material obtained by the preparation method of the present invention are electrical conductivity ≥102% IACS and tensile strength ≥180 MPa, which can meet the application requirements of electronic products and / or power transmission equipment.

[0124] 2. When the proportion of graphene copper powder content in the entire composite material system is too low, the improvement of the overall electrical conductivity and strength of the material is limited (Example 1), and with the increase of content, the electrical conductivity and tensile strength are significantly improved (Examples 2 to 4). In the entire composite material system, graphene constructs an effective conductive network, which helps to improve the electrical conductivity of the composite material. However, when the content of graphene copper powder is too high, the proportion of carbon content in the composite material is relatively high, and graphene agglomeration is prone to occur, which increases the scattering of electron transmission, resulting in a decrease in electrical conductivity. The tensile strength is still gradually improved with the increase of carbon content (Example 4). It can be seen that the content of graphene copper powder has a greater impact on the electrical conductivity of the composite material. Too low or too high will have an adverse effect. In order to obtain better electrical conductivity and strength to meet the application requirements of electronic products and / or power transmission equipment, the reasonable value range of graphene copper powder content is 0.5 to 25wt%.

[0125] 3. When the carbon content of graphene copper powder is low, the graphene content is less, and it is impossible to build an effective conductive bridge to improve the conductivity (Example 5). When the carbon content is high, the graphene is prone to agglomeration and cannot be evenly dispersed in the copper group, increasing the scattering of electron transmission and reducing the conductivity (Example 6). It can be seen that the carbon content will also have a great influence on the conductivity of the composite material, and too low or too high will have an adverse effect; and the tensile strength gradually increases with the increase of carbon content, which is due to the refined grain strengthening and dislocation strengthening mechanism of the formed graphene layer, so that the strength of the composite material is further enhanced. In order to obtain better conductivity and strength to meet the application requirements of electronic products and / or power transmission equipment, the reasonable value range of the graphene copper powder content is 0.05-0.5wt%.

[0126] 4. In the reduction process, low reduction treatment temperature will not completely remove the oxide layer on the surface of the copper powder, which may cause the generated graphene layer and copper to separate at the interface, resulting in decreased conductivity (Example 10); while a high reduction temperature of 300°C may easily cause copper particles to stick together, resulting in poor graphene coating effect, and failure to build a uniform graphene network bridge, which will also lead to decreased guidance (Example 11). Therefore, in order to obtain better conductivity to meet the application requirements of electronic products and / or power transmission equipment, the reasonable range of reduction treatment temperature is 150-300°C.

[0127] 5. In the in-situ carbonization process, low carbonization temperature will lead to incomplete carbonization of the carbon source, poor quality of graphene, and poor conductivity (Example 18). Although high carbonization temperature will make the generated graphene of higher quality, high temperature will cause copper powder to stick together, which will also reduce the carbon content, separate the graphene from the copper interface, and cause the conductivity to decrease (Example 19). As the carbonization time increases, the quality of graphene gradually improves, and the conductivity of the composite material gradually improves (Examples 3 to 20); however, if the carbonization time is further extended, the quality of graphene will gradually decrease, and the phenomenon of interface separation will easily occur, resulting in defects inside the composite material, resulting in a decrease in conductivity (Examples 3 to 21). Therefore, in order to obtain better conductivity to meet the application requirements of electronic products and / or power transmission equipment, the reasonable range of carbonization treatment temperature is 700 to 1000°C, and the reasonable range of treatment time is 20 to 60 minutes.

[0128] 6. In the sintering process, as the sintering temperature increases, the grain size of the composite material increases, the number of grain boundaries decreases, the scattering probability of electron transmission decreases, and the conductivity tends to gradually increase (Examples 3 to 22); however, further increasing the sintering temperature to 1000°C will cause serious agglomeration of graphene at the grain boundaries, increase the scattering of electron transmission, and lead to a decrease in conductivity (Examples 3 to 23); increasing the hot pressing pressure is beneficial to improving the density of the material, reducing defects, and improving conductivity (Examples 3 to 25); as the sintering time increases, the grain size becomes larger, the grain boundaries decrease, and the conductivity gradually increases. However, if the sintering time continues to be extended, more fine grains will appear, the number of grain boundaries increases, the graphene agglomeration begins to intensify, and the conductivity decreases (Examples 3 to 27). Therefore, in order to obtain better conductive properties to meet the application requirements of electronic products and / or power transmission equipment, the reasonable range of sintering temperature is 700-1000°C, the reasonable range of hot pressing pressure is 30-100Mpa, and the reasonable range of sintering time is 10-30min.

[0129] The preparation method of the graphene copper composite material of the embodiment of the present invention utilizes the high catalytic property of the surface of high-purity copper, optimizes the carbon content in the graphene copper powder and the ratio of copper powder and graphene copper powder, adjusts the microstructure and interface structure through the in-situ growth process and sintering process, forms a graphene carbon layer with obvious wrinkle characteristics on the surface of the copper powder, and utilizes the high conductivity and dislocation strengthening mechanism of graphene on the basis of maintaining the high carrier concentration of copper, significantly improving the conductivity and tensile strength of the composite material. The performance indicators of the graphene copper composite material obtained by the preparation method of the present invention meet the conductivity ≥102%IACS, and the tensile strength ≥180MPa; and the preparation method of the present invention is simple in process, easy to control, easy to realize industrial production and application, and is suitable for electronic products and power transmission equipment.

[0130] The above are merely embodiments of the present invention and are not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention are included in the scope of the claims of the present invention to be approved.

Claims

1. A method for preparing a graphene copper composite material, characterized in that: The following steps are involved: In-situ carbonization of copper powder is performed under a carbon source and a protective atmosphere to form graphene on the surface of the copper powder to obtain graphene copper powder, wherein the purity of the copper powder is ≥99.9%; The copper powder and the graphene copper powder are mixed and hot-pressed to obtain the graphene copper composite material; The graphene copper composite material comprises, by weight percentage, 0.5-25wt% of graphene copper powder and the remainder of copper powder; the carbon content in the graphene copper powder is 0.05-0.5wt%.

2. The preparation method according to claim 1, characterized in that: Calculated by weight percentage, the graphene copper composite material comprises: 5-25wt% of graphene copper powder and the remainder of copper powder; the carbon content in the graphene copper powder is 0.12-0.5wt%.

3. The preparation method according to claim 1, characterized in that: Calculated by mass percentage, the graphene copper composite material comprises: 5wt% of graphene copper powder and the remainder of copper powder; the carbon content in the graphene copper powder is 0.12wt%.

4. The preparation method according to claim 1, characterized in that: The copper powder is micron-grade powder, and its particle diameter is 1 to 50 μm.

5. The preparation method according to claim 1, characterized in that: The copper powder is micron-grade powder, and its particle diameter is 3-8 μm.

6. The preparation method according to claim 1, characterized in that: The in-situ carbonization temperature is 700-1000° C., and the carbonization time is 20-60 minutes.

7. The preparation method according to claim 1, characterized in that: The hot pressing sintering temperature is 700-1000° C., the hot pressing pressure is 30-100 MPa, and the sintering time is 10-30 min.

8. The preparation method according to claim 1, characterized in that: Before the step of in-situ carbonizing the copper powder under a carbon source and a protective atmosphere to form graphene on the surface of the copper powder, the method further comprises: The copper powder is subjected to reduction treatment in a reducing atmosphere so that the purity of the copper powder is maintained at not less than 99.9%.

9. The preparation method according to claim 8, characterized in that: The reduction treatment temperature is 150-300° C., and the treatment time is 30-60 minutes.

10. The preparation method according to claim 1, characterized in that: Before the step of in-situ carbonizing the copper powder under a carbon source and a protective atmosphere to form graphene on the surface of the copper powder, the method further comprises: The carbon source and the copper powder are mixed and dissolved in a solvent, and ultrasonic dispersion treatment is performed to obtain a uniform mixture. The mixture is dried and crushed to obtain copper powder coated with the carbon source.

11. The preparation method according to claim 10, characterized in that: The solvent is a mixed solution of water and ethanol in a volume ratio of 1:1-4.

12. The preparation method according to claim 10, characterized in that: In the drying process, the drying temperature is 100-150° C. and the drying time is 1-2 hours.

13. The preparation method according to claim 1, characterized in that: The carbon source is one or more of sucrose, fructose, glucose and maltose.

14. The preparation method according to claim 8, characterized in that: The protective atmosphere is an inert gas, and the reducing atmosphere is a mixed gas consisting of an inert gas and hydrogen.

15. The preparation method according to claim 14, characterized in that: The inert gas flow rate is 0.7 to 1 L / min, and the hydrogen flow rate is 0.3 to 1 L / min.

16. A graphene copper composite material, characterized in that: The compound is prepared by the preparation method according to any one of claims 1 to 15.

17. Use of the graphene copper composite material according to claim 16 in electronic products and / or power transmission equipment.

Citation Information

Cited By

  • Preparation method of graphene coated copper powder

    CN120940641A

  • A method for preparing graphene-coated copper powder

    CN120940641B